Chlorosome antenna complexes from green photosynthetic bacteria - Orf, Gregory S; Blankenship, Robert E (Photosynthesis research, 2013)
Chlorosomes are the distinguishing light-harvesting antenna complexes that are found in green photosynthetic bacteria. They contain bacteriochlorophyll (BChl) c, d, e in natural organisms, and recently through mutation, BChl f, as their principal light-harvesting pigments. In chlorosomes, these pigments self-assemble into large supramolecular structures that are enclosed inside a lipid monolayer to form an ellipsoid. The pigment assembly is dictated mostly by pigment–pigment interactions as opposed to protein–pigment interactions. On the bottom face of the chlorosome, the CsmA protein aggregates into a paracrystalline baseplate with BChl a, and serves as the interface to the next energy acceptor in the system. The exceptional light-harvesting ability at very low light conditions of chlorosomes has made them an attractive subject of study for both basic and applied science. This review, incorporating recent advancements, considers several important aspects of chlorosomes: pigment biosynthesis, organization of pigments and proteins, spectroscopic properties, and applications to bio-hybrid and bio-inspired devices.